2020
DOI: 10.1158/0008-5472.can-19-4032
|View full text |Cite
|
Sign up to set email alerts
|

Y Chromosome LncRNA Are Involved in Radiation Response of Male Non–Small Cell Lung Cancer Cells

Abstract: Numerous studies have implicated changes in the Y chromosome in male cancers, yet few have investigated the biological importance of Y chromosome noncoding RNA. Here we identify a group of Y chromosome-expressed long noncoding RNA (lncRNA) that are involved in male non-small cell lung cancer (NSCLC) radiation sensitivity. Radiosensitive male NSCLC cell lines demonstrated a dose-dependent induction of linc-SPRY3-2/3/4 following irradiation, which was not observed in radioresistant male NSCLC cell lines. Cytogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…More than 50% of breast cancer patients would undergo radiotherapy during their course of treatment. Radiotherapy, in most cases, through X-ray ionizing radiation, inducing damage of DNA via directly or indirectly attacking the backbone of DNA and triggering a sequence of cellular response (12,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of breast cancer patients would undergo radiotherapy during their course of treatment. Radiotherapy, in most cases, through X-ray ionizing radiation, inducing damage of DNA via directly or indirectly attacking the backbone of DNA and triggering a sequence of cellular response (12,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA HOTAIRM1 was reported to be downregulated in papillary thyroid cancer, significantly associated with lymph node metastasis, TNM stage and better prognosis, and suppress cell growth, invasion and migration [27]. In addition, Brownmiller et al found a significant difference in the expression of the Y chromosome lncRNA linc-SPRY3-2/3/4 between radiation-sensitive and radiation-resistant non-small cell lung cancer cells, and confirmed that knockdown of linc-SPRY3-2/3/4 promoted cell viability and resistance to apoptosis after treatment with 8 Gy [28]. In this study, we found that LINC00958 was upregulated in colorectal cancer tissues, which was in accordance with a previous study [29].…”
Section: Discussionmentioning
confidence: 86%
“…For example, lncRNA CRNDE/PRC2 targeting p21 enhance radio-resistance of NSCLC [24]. A recent study revealed that linc-SPRY3-2/3/4, Y chromosome non-coding RNA, regulated radiation sensitivity and affected apoptosis and cell viability in NSCLC [25]. LncRNA PVT1 de ned as a poor prognosis factor, enhances radio-resistance by regulating cell apoptosis in nasopharyngeal carcinoma [26].…”
Section: Discussionmentioning
confidence: 99%